Association of a coding polymorphism in Fc gamma receptor 2A and graft survival in re-transplant candidates - Fuernrohr, Barbara G.; Weiss, Katrin M.; Harre, Ulrike; Wiesener, Michael; Spriewald, Bernd M.; Arnold, Martin (Human Immunology, 2015)
The family of Fc gamma receptors (Fc?Rs) is involved in mediating immunological effector functions. Fc?Rs are differentially expressed on immune cells and can act either activating or inhibitory, with Fc?R2A belonging to the first group. The polymorphism H131R (rs1801274) in FCGR2A has been associated with acute rejection and can shift the overall balance between activating and inhibitory Fc?Rs. Anti-HLA allo-antibodies in transplant recipients have been identified as risk factor for organ survival after transplantation. In this study we genotyped FCGR2A H131R in 200 patients who had undergone kidney transplantation and experienced loss of graft function. FCGR2A polymorphism was related to graft survival and anti-HLA antibodies. Graft survival was calculated as the time interval between transplantation and return to chronic dialysis after transplantation. The gene frequency of FCGR2A R/R131 was found significantly more often in patients with earlier (?60months) compared to patients with later (>60months) graft failure. Overall patients homozygous for R/R131 had a significantly shorter graft survival, compared to H/H131 or H/R131 which is even more pronounced, when anti-HLA antibodies were present. These data suggest, that FCGR2A polymorphisms constitute a risk factor for graft loss following kidney transplantation and that this effect is related to anti-HLA antibodie
EVALuna2:3812